Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1073/pnas.1505370112
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal directionality of DNA mismatch repair in Escherichia coli

Abstract: Defects in DNA mismatch repair (MMR) result in elevated mutagenesis and in cancer predisposition. This disease burden arises because MMR is required to correct errors made in the copying of DNA. MMR is bidirectional at the level of DNA strand polarity as it operates equally well in the 5′ to 3′ and the 3′ to 5′ directions. However, the directionality of MMR with respect to the chromosome, which comprises parental DNA strands of opposite polarity, has been unknown. Here, we show that MMR in Escherichia coli is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
14
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 52 publications
5
14
1
Order By: Relevance
“…This is supported by recent in vivo data indicating that the GATC site distribution influences repair efficiency through determining excision tract length rather than through influencing the efficiency of strand incision (42). …”
Section: Discussionsupporting
confidence: 62%
“…This is supported by recent in vivo data indicating that the GATC site distribution influences repair efficiency through determining excision tract length rather than through influencing the efficiency of strand incision (42). …”
Section: Discussionsupporting
confidence: 62%
“…The mutation spectrum in the uvrAdinBmutS strain is essentially comparable to that in the uvrAdinB strain, with perhaps a slight overall increase ($2-fold). The modest correction efficiency by MMR may reflect that, here, we monitor errors made by Pol V in the context of a gap-filling reaction rather than at a replication fork as previously noted (Hasan and Leach, 2015;Simmons et al, 2008). Lack of efficient MMR correction of Pol z errors has previ-ously been reported in yeast (Aksenova et al, 2010;Lehner and Jinks-Robertson, 2009).…”
Section: Untargeted Base Substitution Mutations: Putative Involvementmentioning
confidence: 76%
“…This differential efficiency of Beta-mediated LT213 recombinants is indicative of heteroduplex plasmid recombination intermediates that form in the absence of DNA replication and that can be subsequently repaired in the Mut + host when the plasmid is replicated. Methyl-directed MMR of the newly replicated, unmethylated DNA strand is coupled to DNA replication ( 46 ). For RecT, we found that the apparent recombination efficiency of oligonucleotide LT213 was ~6-fold lower in a Mut + host than in a mutS mutant host (see Table S3 ).…”
Section: Resultsmentioning
confidence: 99%